CAUSALITY AND VAR ANALYSIS OF TURKISH MILK PRODUCER PRICE - Filiz BASAGAOGLU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this study, there are many influential indicators on the milk producer price which are 4 separate functions: milk production, maize price, clover prices and straw price. This study explores the application of the VAR analysis approach to time series data of producer milk prices covering the period from January 1st, 2010 to December 31st, 2019. The data were taken from the database of the Turkish Statistical Institute. One-way causality relation at 5% level of significance towards milk producer price denoted clover price were detected. In this case, it is possible to say that there is a link between milk producer price and clover price. VAR analysis results show milk production, maize price, clover price and straw price effects on milk producer price.